1998
DOI: 10.1523/jneurosci.18-18-07075.1998
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Stimulation Produces Multiple Forms of Increased Glutamatergic Synaptic Transmission

Abstract: Synaptic modulation and long-term synaptic changes are thought to be the cellular correlates for learning and memory (Madison et al., 1991; Aiba et al., 1994, Goda and Stevens, 1996). The hippocampus is a center for learning and memory that receives abundant cholinergic innervation and has a high density of nicotinic acetylcholine receptors (nAChRs) (Wada et al., 1989; Woolf, 1991). We report that stro ng, brief stimulation of nAChRs enhanced hippocampal glutamatergic synaptic transmission on two independent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(171 citation statements)
references
References 79 publications
8
163
0
Order By: Relevance
“…Therefore, facilitation of mEPSCs was attributed to activation of presynaptic (i.e., expressed directly on presynaptic terminals) and not preterminal nAChRs (i.e., expressed antidromically to presynaptic terminals) (27,57). Activation of presynaptic nAChRs is able to facilitate neurotransmitter release either directly, via increasing Ca 2ϩ influx through nAChR-mediated ion channels, or indirectly, via causing transient depolarization of presynaptic terminals and activation of presynaptic VACCs (15,19,24,27,39,45,47,56). To distinguish between these two possibilities, nicotine-mediated facilitation of mEPSCs in the caudal NTS was investigated using potent antagonists of HVACCs and LVACCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, facilitation of mEPSCs was attributed to activation of presynaptic (i.e., expressed directly on presynaptic terminals) and not preterminal nAChRs (i.e., expressed antidromically to presynaptic terminals) (27,57). Activation of presynaptic nAChRs is able to facilitate neurotransmitter release either directly, via increasing Ca 2ϩ influx through nAChR-mediated ion channels, or indirectly, via causing transient depolarization of presynaptic terminals and activation of presynaptic VACCs (15,19,24,27,39,45,47,56). To distinguish between these two possibilities, nicotine-mediated facilitation of mEPSCs in the caudal NTS was investigated using potent antagonists of HVACCs and LVACCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common presynaptic or preterminal nAChR in the CNS is composed of ␣7-subunits (1,14,16,19,35,39,42). Activation of presynaptic nAChRs is able to facilitate neurotransmitter release either directly, via increasing Ca 2ϩ influx through nAChR-mediated ion channels (15,19,24,27,39,45), or indirectly, via transient depolarization and activation of voltage-activated Ca 2ϩ channels (VACCs) (27,47,56). The mechanisms of nAChR-mediated facilitation of synaptic glutamate release in the caudal NTS remain unknown and are investigated in the present study using patch-clamp electrophysiology, fluorescent Ca 2ϩ imaging, and rat horizontal brainstem slices.…”
mentioning
confidence: 99%
“…In the mammalian brain, ␣7 and ␣4␤2 nAChRs control synaptic transmission mediated by the major inhibitory and excitatory neurotransmitters, ␥-aminobutyric acid (GABA) and glutamate, respectively (McMahon et al, 1994;Gray et al, 1996;Lindstrom et al, 1996;Role and Berg, 1996;Albuquerque et al, 1997;Alkondon et al, 1997aAlkondon et al, , 1999Alkondon et al, , 2000cBertolino et al, 1997;Léna and Changeux, 1997;Wonnacott, 1997;Radcliffe and Dani, 1998;Ji and Dani, 2000;Alkondon and Albuquerque, 2001) and mediate fast synaptic transmission (Zhang et al, 1993;Roerig et al, 1997;Alkondon et al, 1998;Frazier et al, 1998;Hatton and Yang, 2002). Certain aspects of neuronal proliferation, differentiation and death, are also modulated by ligands interacting with ␣7 and ␣4␤2 nAChRs in the brain (Berger et al, 1998;Broide and Leslie, 1999;Belluardo et al, 2000;Coronas et al, 2000;Dajas-Bailador et al, 2002;Falk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…α7-like), whereas those involved in 5HT release are not . Indeed, depending on the pattern of nicotine application, both α7 and non-α7 receptors may enhance glutamate release in rat hippocampal micro-island cultures (Radcliffe & Dani, 1998). Nicotinic enhancement of GABA release in hippocampus is likely to be mediated by both α7 and non-α7 receptors (Alkondon et al, 1999;Maggi et al, 2001).…”
Section: Receptor Typesmentioning
confidence: 99%
“…It has been reported that activation of presynaptic nicotinic receptors results in increases in the amplitude of submaximal glutamatergic synaptic currents Bordey et al, 1996;Radcliffe & Dani, 1998;Mansvelder & McGehee, 2000) or in the increase in the non-NMDA component and decrease in the NMDA one (Fisher & Dani, 2000). Important modulatory effects on synaptic plasticity have also been described (Mansvelder & McGehee, 2000;Ji et al, 2001).…”
Section: Receptor Typesmentioning
confidence: 99%